Research on modified teaching-learning-based optimisation algorithm for estimating parameters of Van Genuchten equation. (2017) - Gu, Fahui; Huang, Ying; Liu, Yue
In this paper, a modified teaching-learning-based optimisation (MTLBO) algorithm is proposed for estimating parameters of Van Genuchten equation. A self-adaptive mutation strategy is used to overcome local convergence of the teaching-learning-based optimisation (TLBO). The proposed method is applied to MATLAB test system and the simulation results are compared with other algorithms which verify the superiority of the proposed method. It shows that the MTLBO algorithm is an effective method for estimating parameters of Van Genuchten equation.